Hadith Concerning Bathing the Dead: Its Implementation at PKU Muhammadiyah Hospital Yogyakarta - Rika Andriana; Jannatul Husna; Gamal Abdul Nasir Zakaria (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
Bathing the corpse is one form of farḍu kifāyah in Islam. In Yogyakarta, the practice of bathing the corpse has been facilitated by one of them, PKU Muhammadiyah Hospital Yogyakarta. Due to the legality of the community institution, the author feels the need to examine the form of implementation (practice), basis, and validity of the evidence for bathing the corpse. This type of research is qualitative field research with interview, observation and documentation data collection techniques. Furthermore, to understand the meaning of the hadith, the researcher uses the methodology of understanding the hadith of Arifuddin Ahmad, with textual, intertextual and contextual interpretation methods. In this study, it was found that the practice of bathing the corpse at PKU Muhammadiyah Hospital Yogyakarta in its implementation begins with determining who will bathe the corpse, which begins with the intention, placing the corpse in a closed room and ending with maintaining the corpse's disgrace. In this case, there is a discrepancy between the text of the hadith and its implementation. Such as bathing a person who died from burning, in terms of braiding and the use of inconsistent wet cloth.